Managing cultural diversity through communication: A face negotiation perspective on Muslim and Aboge interactions in Wonosobo - Fabriar, Silvia Riskha; Nur Fitri, Alifa; Fitri, Fitri; Rachmawati, Farida (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This research discusses the communication between Muslims and Aboge adherents in Mudal Urban Village, Wonosobo, using the Face Negotiation theory. The main focus of this research is how effective communication creates social harmony in the midst of community diversity. This research uses a descriptive qualitative approach, with data obtained through observation, interviews, and documentation. The results show that harmonious communication patterns are realized through facework that prioritizes respect for other groups and mindfulness. Traditions such as selametan and community service become interaction spaces that strengthen emotional relationships with a collectivist approach and a combination of direct and indirect communication. Face negotiation strategies play an important role in maintaining group honour while managing differences without conflict. Effective communication allows Muslim and Aboge communities to coexist inclusively, strengthening social cohesion and making diversity an asset for community harmony. This study contextualizes the Face Negotiation Theory in a local context while emphasizing the role of communication in building social harmony based on cultural values. ***** Penelitian ini mengkaji komunikasi antara masyarakat Muslim dan penganut adat Aboge di Kelurahan Mudal, Wonosobo, dengan menggunakan teori negosiasi wajah. Fokus utama penelitian ini adalah bagaimana komunikasi efektif menciptakan harmoni sosial di tengah keberagaman masyarakat. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan data diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pola komunikasi harmonis terwujud melalui facework yang mengedepankan penghormatan terhadap kelompok lain dan mindfulness. Tradisi seperti selametan dan kerja bakti menjadi ruang interaksi yang memperkuat hubungan emosional, dengan pendekatan kolektivisme dan kombinasi komunikasi langsung dan tidak langsung. Strategi face negotiation memainkan peran penting dalam menjaga kehormatan kelompok sambil mengelola perbedaan tanpa konflik. Komunikasi yang efektif memungkinkan masyarakat Muslim dan Aboge untuk hidup berdampingan secara inklusif, memperkuat kohesi sosial, dan menjadikan keberagaman sebagai aset harmoni masyarakat. Penelitian ini berkontribusi untuk mengontekstualisasikan teori negosiasi wajah dalam konteks lokal sekaligus menegaskan peran komunikasi dalam membangun harmoni sosial berbasis nilai budaya.